Targeting natural killer cell reactivity by employing antibody to NKp46: implications for type 1 diabetes. - Rami Yossef; Chamutal Gur; Avishai Shemesh; Ofer Guttman; Uzi Hadad; Shlomo Nedvetzki; Antonija Miletić; Karen Nalbandyan; Adelheid Cerwenka; Stipan Jonjic; Ofer Mandelboim; Angel Porgador (PLoS ONE)
Natural killer (NK) cells belong to the innate lymphoid cells. Their cytotoxic activity is regulated by the delicate balance between activating and inhibitory signals. NKp46 is a member of the primary activating receptors of NK cells. We previously reported that the NKp46 receptor is involved in the development of type 1 diabetes (T1D). Subsequently, we hypothesized that blocking this receptor could prevent or hinder disease development. To address this goal, we developed monoclonal antibodies for murine NKp46. One mAb, named NCR1.15, recognizes the mouse homologue protein of NKp46, named Ncr1, and was able to down-regulate the surface expression of NKp46 on primary murine NK cells following antibody injection in vivo. Additionally, NCR1.15 treatments were able to down-regulate cytotoxic activity mediated by NKp46, but not by other NK receptors. To test our primary assumption, we examined T1D development in two models, non-obese diabetic mice and low-dose streptozotocin. Our results show a significantly lower incidence of diabetic mice in the NCR1.15-treated group compared to control groups. This study directly demonstrates the involvement of NKp46 in T1D development and suggests a novel treatment strategy for early insulitis.